Exact constants in Jackson-type inequalities for L_2-approximation on an axis - Doronin, V. G.; Ligun, A. A.; Serdyuk, A. S.; Shydlich, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We investigate exact constants in Jackson-type inequalities in the space L_2 for the approximation of functions on an axis by the subspace of entire functions of exponential type.